2006
DOI: 10.1111/j.1365-2141.2006.06344.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an adult blood‐derived progenitor cell population capable of differentiation into angiogenic, myocardial and neural lineages

Abstract: SummaryBlood-derived adult stem cells were previously considered impractical for therapeutic use because of their small numbers. This report describes the isolation of a novel human cell population derived from the peripheral blood, termed synergetic cell population (SCP) Neural cell precursors (NCPs) expressed the neuronal markers Nestin, bIII-Tubulin, and Neu-N, the glial markers GFAP and O4, and responded to neurotransmitter stimulation. Myocardial cell precursors (MCPs) expressed Desmin, cardiac Troponin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
0
43
0
2
Order By: Relevance
“…With this background, EPCs could be important in the homeostasis of the nutritive microvasculture, and their exhaustion or dysfunction may accelerate the course of diabetic neuropathy. Moreover, as progenitor cells derived from the adult blood can be differentiated also toward the neural phenotype (73), it is possible that a broader derangement of immature circulating cells in diabetes predisposes to this chronic complication, dowregulating both endothelial and neuronal progenitors. Unfortunately, no study to date has directly explored these hypotheses.…”
Section: Epcs and Diabetic Neuropathymentioning
confidence: 99%
“…With this background, EPCs could be important in the homeostasis of the nutritive microvasculture, and their exhaustion or dysfunction may accelerate the course of diabetic neuropathy. Moreover, as progenitor cells derived from the adult blood can be differentiated also toward the neural phenotype (73), it is possible that a broader derangement of immature circulating cells in diabetes predisposes to this chronic complication, dowregulating both endothelial and neuronal progenitors. Unfortunately, no study to date has directly explored these hypotheses.…”
Section: Epcs and Diabetic Neuropathymentioning
confidence: 99%
“…However, these results have been recently questioned by another group using similar experimental conditions (17). Furthermore, most in vitro studies were limited to the evaluation of myocardial markers expression and did not examine whether HSCs had acquired myocardial functional properties as well (7,16,26,40). Therefore, it remains to be convincingly shown that HSCs can differentiate into functional myocardial cells in vitro.…”
mentioning
confidence: 99%
“…The progenitor cells differentiated into a variety of cell lineages on defined culture conditions. The resulting cells exhibited morphological, immunocytochemical and Advances in Biomedicine and Pharmacy (An International Journal of Biomedicine, Natural Products and Pharmacy) functional characteristics of angiogenic, neural or myocardial lineages [2]. The isolation of pluripotent precursor cells from equine peripheral blood was tested for their differentiation potential and it was found that equine peripheral blood-derived cells had osteogenic and adipogenic differentiation capacities comparable to cells derived from bone marrow [3].…”
Section: Introductionmentioning
confidence: 99%